The Potential of Aloe vera and Opuntia ficus-indica Extracts as Biobased Agents for the Conservation of Cultural Heritage Metals - Çağdaş Özdemir; Lucia Emanuele; Marta Kotlar; Marina Brailo Šćepanović; Laura Scrano; Sabino Aurelio Bufo (Metabolites, 2025)
Background/Objectives: Biocorrosion, driven by microbial colonization and biofilm formation, poses a significant threat to the integrity of metal artifacts, particularly those composed of copper and its alloys. Pseudomonas aeruginosa, a bacterial species that reduces nitrates, plays a key role in this process. This study explores the potential of two metabolite-rich plant extracts, Aloe vera and Opuntia ficus-indica, as sustainable biobased inhibitors of microbial-induced corrosion (MICOR). Methods: The antibacterial and antibiofilm activities of the extracts were evaluated using minimal inhibitory concentration (MIC) assays, time-kill kinetics, and biofilm prevention and removal tests on copper, bronze, and brass samples. Spectrophotometric and microbiological methods were used to quantify bacterial growth and biofilm density. Results: Both extracts exhibited significant antibacterial activity, with MIC values of 8.3% (v/v). A. vera demonstrated superior bactericidal effects, achieving reductions of ≥3 log10 in bacterial counts at lower concentrations. In antibiofilm assays, both extracts effectively prevented biofilm formation and reduced established biofilms, with A. vera exhibiting greater efficacy against them. The active metabolites—anthraquinones, phenolics, flavonoids, and tannins—likely contribute to these effects. Conclusions: These findings highlight the dual role of A. vera and O. ficus-indica extracts as both corrosion and biocorrosion inhibitors. The secondary metabolite profiles of these plants support their application as eco-friendly alternatives in the conservation of metal cultural heritage objects.